Navigating Financial Performance: The Influence of NPL and LDR on ROA with Inflation as a Moderating Factor - Deny Hidayat; Sakifah Sakifah; Noneng Masitoh (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study investigates the impact of Non-Performing Loans (NPL) and Loan to Deposit Ratio (LDR) on Return on Assets (ROA) in Indonesian banking from 2017 to 2023, with inflation examined as a moderating factor. Using panel data regression analysis on 301 observations from 43 banking companies listed on the Indonesia Stock Exchange, the study finds that NPL negatively affects ROA but lacks statistical significance, contrary to expectations from the bad management hypothesis. In contrast, LDR positively and significantly influences ROA, supporting the Anticipated Income theory. Moderation analysis reveals that inflation does not significantly moderate the relationships between NPL and ROA, nor LDR and ROA. These findings suggest that while inflation impacts economic conditions and investment decisions, its direct effect on bank profitability through NPL and LDR is limited. The findings imply that enhancing managerial competencies in credit assessment and risk management is crucial for mitigating NPL risks and improving bank profitability. Banks should also prudently manage LDR to maximize profitability while considering credit risk. Effective inflation risk management strategies are recommended despite its minimal direct impact on NPL and LDR effects on ROA. Future research should explore additional factors influencing these relationships, including regulatory policies and macroeconomic conditions.